Peningkatan Pemahaman Investasi pada Siswa SMK Logistik Sumedang - Retno Widya Ningrum; Irfan Achmad Musadat; Agung Achmad Pramayuda; Aninditha Putri Kusumawardhani; Okta Eka Putra (Jurnal Bhakti Karya dan Inovatif, 2024)
The young generation is investment literate and is important in future economic development. Investment is aimed at getting more value in the future from consumption that is withheld in the present (Ekananda, 2018). Meanwhile, an investment decision is an action that goes through thinking about the benefits and risks that will be faced from choosing the investment (Milzam et al., 2024). So, before making an investment decision, the community must have adequate knowledge about investment. The target participants in this Community Service activity are students of Logistics Vocational School. Current Logistics Vocational School students are Gen-Z. Gen-Z is a generation estimated to be born between 1995 and 2012 (Sawitri, 2023). Gen-Z has one of the characteristics, namely being very tech-savvy and daring to take risks. Graduates of SMK Logistik Sumedang will become the community that continues the Indonesian economy. The method used in this Community Service activity at SMK Logistik Sumedang is the service learning approach. Rahdiyanta and Hidayat (2016) and Rusli et al. (2022) stated that this methodology is suitable for use in the world of education because it is a combination of community experience and academic knowledge. This methodology aims to provide direct contributions through delivering materials such as teaching to students so that students' understanding of investment is increased. Based on the results of Community Service activities at SMK Logistik Sumedang, students have high enthusiasm for investment, especially in instruments with low investment amounts starting from IDR 10,000 such as mutual funds or saving gold through digital investment platforms.